Economic valuation of ecosystem services of natural plant associations of the Pluzhne forestry - Radomska, Marharyta M.; Tykhenko, Oksana M.; Nazarkov, Taras I. (Kyiv National University of Construction and Architecture, 2023)
Ecosystem services are the basis of human development and existence. The resilience and balance of ecosystems is the key to the well-being and comfort of the human race, but their role and value of services provided is often underestimated. The aim of the given research is to conduct economic assessment of ecosystem services of natural plant associations of the selected area – Pluzhne forestry. Forests are known to provide the most diverse and comprehensive complex of ecosystem services and thus represent complicated object for assessment. The first step of the assessment included formulation of the list of ecosystem services to be included into the assessment procedure, giving priority to the most well-studied. The second step was aimed at determination of the unit prices for the chosen services. They were elaborated based on similar valuations, sufficiently supported by research data. The resulted cost of ecosystem services provided were compared to the assessments, performed for forest ecosystems in Ukraine and European countries, which is an element of novelty and originality. Although there are noticeable deviations in specific value of ecosystem services per unit of forest area, the general trend in consistent with European experience. The reasons of differences could be explained by the choice of approaches to unit prices evaluation and list of services included into assessment. The obtained data are important for raising awareness of local population and authorities about the importance of ecosystems functioning and need to invest resources in their support and protection. Research works of such kind are still rare in Ukrainian academic sphere despite their high importance for efficient management of environment quality and use. Thus, there is a clear need develop this research field and the given research contributes theoretical and applied provisions for further assessments of such kind.